Evidence-based practice in athletic training - Raab, S.; Craig, D. I. (Human Kinetics, 2016)
As one of the first texts of its kind, Evidence-Based Practice in Athletic Training contains essential information on the fundamentals of evidence-based practice (EBP) for students who are working toward certification in athletic training and athletic trainers who wish to stay up to date on best practices in the field. With EBP, all clinical decisions are based on available research studies, and these studies are selected and assessed according to specific criteria that yield evidence of benefit. EBP is a continuing education requirement for athletic trainers who are certified with the Board of Certification (BOC).